Subnanometer poly-silicon gap structure formation: Comparison study between size expansion and size reduction - Uda, Hashim, Prof. Dr.; Nazwa, Taib; Thikra, S. Dhahi (American Institute of Physics., 2013)
Link to publisher's homepage at http://www.aip.org/